Monitoring spray drift in aerial spray application based on infrared thermal imaging technology - Jiao, Leizi; Dong, Daming; Feng, Haikuan; Zhao, Xiande; Chen, Liping (Computers and electronics in agriculture, 2016)
•A first study to measure pesticide drift distribution using thermal imaging.•Tiny thermal differences during spray application had been measured.•The drift distribution and spray range could be detected.•The testing results had well agreement with the water-sensitive paper method. The pesticide drift in aerial spray applications is harmful both to environment and human beings but hard to be measured. We demonstrated a new method for real-time evaluation of pesticide drift which used infrared thermal imaging technology to detect the thermal differences before and after spraying process and then measured the range and concentration distribution of droplets. The drift distribution and spray range are detected using infrared thermal imaging system combined with image processing algorithms. The experiments were carried out in both ground spray and aerial spray applications. The results showed that this method had the ability to detect the tiny thermal differences during spray application and thus to monitor the aerial drifts. Furthermore, the testing results using this method had well agreement with the water-sensitive paper method. Therefore, it is verified that infrared thermal imaging method combined with infrared image processing algorithms can be used to monitor the pesticide drift in aerial spray application with advantages of fast, non-contact and able to realize real-time measurement.